Effects of neuromodulation techniques on pain and depression in patients with phantom limb pain: a systematic review and meta-analysis - Tao, Xu-chen; Ma, Shujie; Gong, Jingwen; Zhu, Jianzhong; Wang, Jinxiang; Wu, Baoyu; Zhu, Yan; Liu, Xinhao; Fang, Lei (Frontiers in Neurology, 2025)
ObjectiveThis systematic review and meta-analysis aimed to evaluate the efficacy of neuromodulation techniques in alleviating pain and depression in patients with phantom limb pain (PLP).MethodsWe conducted a comprehensive search of five databases (Medline, Scopus, Embase, Cochrane Library, and Web of Science) up to March 2025, following PRISMA guidelines. Randomized controlled trials (RCTs) investigating central (e.g., rTMS, tDCS) and peripheral (e.g., TENS, NMES, PNS) neuromodulation techniques in PLP patients were included. Primary outcomes were pain reduction, measured by the Visual Analog Scale (VAS) and McGill Pain Questionnaire (MPQ), and depression, assessed using the Beck Depression Inventory (BDI) and Self-Rating Depression Scale (SDS). Data were extracted and analyzed using Review Manager and Stata, with heterogeneity assessed via the I2 statistic and Q test.Results17 RCTs involving 510 patients were included. Central neuromodulation techniques, particularly rTMS and tDCS, significantly reduced pain in PLP patients [excitatory M1 rTMS: MD = −1.45, 95%CI (−2.78, −0.11), p = 0.03; anodal M1 tDCS: MD = −1.60, 95%CI (−2.45, 0.74), p = 0.0003]. tDCS with duration >15 min [I2 = 12%, MD = -1.91, 95%CI (−3.10, 0.72), p = 0.002] and rTMS>7 days treatment [MD = -4.35, 95%CI(−6.34,-2.36), p < 0.0001] were observed significant pooled effects. Peripheral techniques, including TENS and PNS, also showed pain relief, though with fewer studies. No significant improvement in depression.ConclusionNeuromodulation techniques, particularly rTMS and tDCS, are effective in reducing PLP but do not significantly alleviate depression. Further large-scale RCTs with longer follow-ups are needed to confirm these findings and explore the efficacy of other neuromodulation methods.Systematic review registrationPROSPERO CRD42022314995.